A 12-Month Prospective Cohort Study of Symptoms of Common Mental Disorders Among European Professional Footballers. Issue 5 (September 2017) - Gouttebarge, Vincent; Aoki, Haruhito; Verhagen, Evert A. L. M.; Kerkhoffs, Gino M. M. J.
Abstract : Objective: To determine the 12-month incidence and comorbidity of symptoms of common mental disorders (CMD) among European professional footballers and to explore the association of potential stressors with the health conditions under study among those European professional footballers. Design: Observational prospective cohort study with a follow-up period of 12 months. Participants: Male professional footballers from 5 European countries (n = 384 at baseline). Assessment of Risk Factors: Adverse life events, conflicts with trainer/coach, and career dissatisfaction were explored by using validated questionnaires. Main Outcome Measures: Symptoms of distress, anxiety/depression, sleep disturbance, and adverse alcohol use were assessed using validated questionnaires. Results: A total of 384 players (mean age of 27 years old; mean career duration of 8 years) were enrolled, of which 262 completed the follow-up period. The incidence of symptoms of CMD were 12% for distress, 37% for anxiety/depression, 19% for sleep disturbance, and 14% for adverse alcohol use. Over the follow-up period of 12 months, approximately 13% of the participants reported 2 symptoms, 5% three symptoms, and 3% four symptoms. Professional footballers reporting recent adverse life events, a conflict with trainer/coach, or career dissatisfaction were more likely to report symptoms of CMD, but statistically significant associations were not found. Conclusions: The 12-month incidence of symptoms of CMD among European professional footballers ranged from 12% for symptoms of distress to 37% for symptoms of anxiety/depression. A professional football team typically drawn from a squad of 25 players can expect symptoms of CMD to occur among at least 3 players in one season.